THE USE OF BODY CAMERAS BY LAW ENFORCEMENT OFFICERS AS A TOOL FOR PROMOTING THE PRINCIPLE OF ADMINISTRATIVE MORALITY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This paper analyzes the relationship between the use of body cameras by law enforcement officers and the effectiveness of the principle of administrative morality. Starting from a contextualization of the State's police power and the challenges of curbing abuse of power, the study explores body cameras as a tool for controlling and ensuring transparency in police activity. It examines initiatives that seek to regulate the use of cameras, highlighting Ministry of Justice Ordinance No. 648/2024, which establishes guidelines and mandates the use of cameras in a variety of situations. The paper also addresses administrative morality as a principle that guides the actions of Public Administration, demanding ethical, transparent, and public interest-oriented conduct. It briefly demonstrates how body cameras can contribute to the realization of morality in public safety, preventing abuses and promoting public trust, and how changes in the Law on Administrative Impropriety, which may hinder the accountability of public officials in cases of misconduct, do not prevent the configuration and punishment of an act of administrative impropriety. Therefore, this paper is based on the hypothesis that the non-use of body cameras by members of public security agencies in accordance with Ministry of Justice Ordinance No. 648/2024 violates the principle of administrative morality, since the effectiveness of this principle also depends on police control tools such as the widespread use of body cameras, a hypothesis that is tested using the hypothetical-deductive method.